2016
DOI: 10.1038/srep23544
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Differentiation Potency of Mesenchymal Stromal Cells from Perinatal Tissues

Abstract: Human perinatal tissue is an abundant source of mesenchymal stromal cells(MSCs) and lacks the ethical concerns. Perinatal MSCs can be obtained from various tissues as like amnion, chorion, and umbilical cord. Still, little is known of the distinct nature of each MSC type. In this study, we successfully isolated and cultured MSCs from amnion(AMSCs), chorion(CMSCs), and umbilical cord(UC-MSCs). Proliferation potential was different among them, that AMSCs revealed the lowest proliferation rate due to increased An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 45 publications
4
72
0
2
Order By: Relevance
“…Our findings establish that AF‐MSCs from two AF sources differentiate into neuron‐like cells with typical morphological changes, showing trans‐differentiation potential from a mesenchymal to neural lineage despite the fact that MSCs are considered being distant from neural cells. This observation is consistent with the results from the previous studies using MSCs from prenatal tissues and amniotic fluid (Prusa et al, ; Chen et al, ; Kwon et al, ). The spontaneous expression of several neural markers (including Nestin ) in undifferentiated MSCs from various sources has been considered as an evidence of the cell predisposition to differentiate toward neural lineages (Foudah et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings establish that AF‐MSCs from two AF sources differentiate into neuron‐like cells with typical morphological changes, showing trans‐differentiation potential from a mesenchymal to neural lineage despite the fact that MSCs are considered being distant from neural cells. This observation is consistent with the results from the previous studies using MSCs from prenatal tissues and amniotic fluid (Prusa et al, ; Chen et al, ; Kwon et al, ). The spontaneous expression of several neural markers (including Nestin ) in undifferentiated MSCs from various sources has been considered as an evidence of the cell predisposition to differentiate toward neural lineages (Foudah et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, no evidence exists that AF‐MSCs from AF of fetus‐diseased gestations have the capability to neural or myogenic differentiation. Recent studies have shown that MSCs isolated from perinatal tissues can differentiate into cells of neuroectodermal lineage (Tamagawa et al, ; Kwon et al, ). MSCs derived from AF or amniotic membrane generated terminally differentiated neural cells expressing neurotransmitters, brain‐derived and nerve growth factors, which lead to bio‐delivery and regeneration of the damaged tissue (Pan et al, ; Yan et al, ; Kim et al, ; Maraldi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Human UC‐MSCs and AM‐MSCs generally fulfill the minimal criteria for the definition of MSCs. However, perinatal MSCs have previously been demonstrated to possess an innate tissue‐specific characteristic, including differentiation potency, which is genetic background independent . Results presented by Wegmeyer et al suggest that AM‐MSCa and UC‐MSCs possess weaker osteogenic and adipogenic activity in comparison to adult MSCs .…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are known to be strongly involved in angiogenesis and vasculogenesis through direct differentiation as well as paracrine activities [4, 6]. Kwon et al [30] underlined the tissue-specific differentiation potential and genetic programs in MSCs. Former results from our laboratory also described different regenerative capacities of MSCs depending on their origin [3].…”
Section: Discussionmentioning
confidence: 99%